Protective effect of selenium against oxidative stress for biochemical and blood parameters in Ovariectomyzed and cadmium exposured female rats - Talib Hussen Ali; Ahmed Baker Ali; Heyam Natheer Matti (College of Education for Pure Sciences, 2012)
Abstract The present investigation was aimed the possibility protective effect of Se‌lenium chloride against oxidative stress during Ovariectomy and Ovariectomy - cadmium chloride exposure, (25) female rats Albino Wister type weighting (250- 300g). Rats were randomly divided to five experimental groups, including (5) animals each group. The first group gives normal chow diet (negative control). The second group gives normal chow diet with ovariectomized rat (positive control /Ovx). And three experimentally groups. Ovariectomized (Ovx) sexually mature adult female rats were exposed to sub chronic treatment of cadmium chloride (CdCl) at a dose of 6 mg/kg B.W/rat then, were orally gavaged daily with 2ml of the treatment for a period of 28 days, the results show that there was significant reduction in Erythrocytes count (RBCs), Hematocrit percentage P.C.V. (Hct%) and Hemoglobin value (Hb), While mean corpuscles hemoglobin concentration (MCHC) was increased. More- over, hepatic and renal antioxidant enzymes activities, peroxidase and Catalase (CAT) were decreased significantly in comparison with the control. The consequences of ovariectomy operation of female rats exhibited the same values for all of the above mentioned Ovx-Cd treatment parameters. Both the experimental rat groups (Ovx and Ovx-Cd) were gavaged orally with a 2 ml solution of the dietary supplementation (selenium chloride SeCl) individually or in combination with CdCl at a dose of6 mg/kg.B.W, resulting recovery effects for blood parameters and antioxidant enzymatic activities were almost restored to control level, except for peroxidase activity that was respond differently in both type of treatment. The present study revealed significant protective action of selenium on the toxicity induced by Ovx or Ovx-Cd in female rats, especially when selenium was subsequently supplemented to both treatments